2015
DOI: 10.1159/000439278
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of High-Dose Vitamin D on the Level of Interleukin 10 in Patients with Multiple Sclerosis: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Background: Multiple sclerosis (MS) is a chronic demyelinating disease of the central nervous system. Vitamin D has been related to the prevention of MS and to modulating its course. Recent studies have shown the safety of high-dose vitamin D in MS. Objective: This study compared the effects of high-dose vitamin D on interleukin 10 (IL-10) levels in MS patients in a double-blind, randomized clinical trial. Methods: Ninety-four patients with relapsing remitting MS (RRMS) were randomized into a treatment and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 24 publications
2
47
0
Order By: Relevance
“…In addition, the UVB-dependent generation of bioactive Vitamin D and its relevance for MS have been studied over decades, since high serum levels of Vitamin D correlate with low incidence and disease activity, thus representing both a mechanistic explanation for the latitude gradient as well as a druggable target for MS 27,28 . However, even though recent clinical studies showed a decrease in inflammatory cytokine serum levels of Vitamin D treated patients 29 , an intervention study using Vitamin D2 failed to show effectiveness of the treatment, but, in contrast, demonstrated increased disease scores in the treatment group after the study period 30 . Thus, changes in Vitamin D levels might represent an epiphenomenon of sun exposure rather than an explanation for the latitude gradient or a druggable target for therapeutic intervention in MS.…”
Section: Geographic Factors and Sun Exposurementioning
confidence: 94%
“…In addition, the UVB-dependent generation of bioactive Vitamin D and its relevance for MS have been studied over decades, since high serum levels of Vitamin D correlate with low incidence and disease activity, thus representing both a mechanistic explanation for the latitude gradient as well as a druggable target for MS 27,28 . However, even though recent clinical studies showed a decrease in inflammatory cytokine serum levels of Vitamin D treated patients 29 , an intervention study using Vitamin D2 failed to show effectiveness of the treatment, but, in contrast, demonstrated increased disease scores in the treatment group after the study period 30 . Thus, changes in Vitamin D levels might represent an epiphenomenon of sun exposure rather than an explanation for the latitude gradient or a druggable target for therapeutic intervention in MS.…”
Section: Geographic Factors and Sun Exposurementioning
confidence: 94%
“…At the end of the study, the researchers found that IL-10 levels increased significantly after taking the high-dose vitamin D3 for three months. They concluded that high doses of vitamin D could be valuable in promoting an anti-inflammatory state in RRMS patients (Ashtari et al, 2015). Fitzgerald et al (2015) studied the relationship between 25-hydroxyvitamin D (25[OH] D) levels and disease course in patients with RRMS treated with interferon beta-1b.…”
Section: Resultsmentioning
confidence: 99%
“…Daily vitamin D supplementation for 35 days increased IL‐10 in vitamin D insufficient subjects (serum 25(OH)D < 29 ng/mL) (Barker et al, ). Furthermore, three month supplementation with 50000 IU vitamin D for 3 month increased IL‐10 in multiple sclerosis (Ashtari, Toghianifar, Zarkesh‐Esfahani, & Mansourian, ). IL‐10 is an anti‐inflammatory cytokine that can reduce the oxidative stress and amplify insulin sensitivity (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…increased IL-10 in multiple sclerosis (Ashtari, Toghianifar, Zarkesh-Esfahani, & Mansourian, 2015). IL-10 is an anti-inflammatory cytokine that can reduce the oxidative stress and amplify insulin sensitivity (Zhang et al, 2017).…”
Section: Ta B L E 3 Effects Of Vitamin D On Omentin Vaspin An Inflammentioning
confidence: 99%